Aplicativo móvil multiplataforma para la ubicación y reserva de canchas sintéticas en la ciudad de Iquitos, 2022 - Tapullima del Aguila, Angelo (2024)
The objective of this research was to determine whether the use of a mobile application could improve the process of locating and reserving sports fields in the city of Iquitos in 2022. The research was a pure experimental type with an experimental design, which included a study group where the Pre-test and Post-test method was used. The sample consisted of 50 people between the ages of 18-50. A non-probabilistic convenience sampling was used to select the participants, and surveys and observation sheets were used as data collection instruments. SPSS was the software used for data analysis. The results indicate that the multiplatform mobile application for the location and reservation of sports fields is useful and significantly improves the time to find a sports venue, the average time to reserve a sport field, the average cost of reserving a sport field, the level of User satisfaction and the difference in the average time to locate courts according to the user's location. In conclusion, the use of a mobile application satisfactorily improves the process of locating and reserving synthetic field in the city of Iquitos.